Rancang Bangun Sistem Pendukung Keputusan Seleksi Penerimaan Siswa Baru dengan Metode Fuzzy Tahani (Studi Kasus di SMK Migas Cepu) - Joko Handoyo (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2016)
Selection of new students is a process of screening and selection of students whose academic ability is the best candidate to study in aneducational institution that needs to be determined quickly and accurately. In terms of determination of new student candidates it isnecessary to consider several considerations that are quite complicated and that is the standardization of values, school entry requirementsand policies of government and educational institutions that change frequently every year. Schools that many parents choose as a place fortheir children to go to school is a favorite school. Favorite schools in society, have parameters that become the needs of society. So it can beconcluded, the choice of society to a school is a rational consideration based on the wishes of parents for their sons and daughters get adecent education and quality. The process of assessing the selection of new admissions is done by more than one assessor, so that it needs toinfer the value data. Previously the conclusion process is still experiencing difficulties, especially for subjective value data (value is obtainedbased on one's point of view). Based on these matters, the authors conduct research on the need for new admissions selection to obtain abenchmark development of a new decision support selection selection system. This application is a decision support system, which aims toprovide support for manager's consideration without having to replace the manager function. In research, the system aims to providesupport to the school in determining the selection of new student candidates. Furthermore, the decision-making process until the evaluationstage of alternative selection. This is useful for facilitating decision-makers related to the selection problem of new admissions, so that willget the most worthy students received at the school. In the study, alternative decisions in the form of new prospective students, while theattributes in the form of assessment elements tailored to the needs of the school. The need for different new admissions selection and thenumber of irregular assessors or more than one person led to the need for a better method of completion in the process of selecting newstudents. The method used in decision selection selection of new students is Fuzzy Tahani Logic. With the application of decision supportsystem selection selection of new students is expected to facilitate decision makers to be expected to help and facilitate the assessment teamin determining new students who are eligible to be accepted. The result of the highest percentage value in this study, the success of decisionsupport system for new admissions candidate based on fuzzy tahani method is Value a = 0.60, Value b = 0.75, Value c = 0.99.